Effect of Soil Burial on Tensile Properties of Polypropylene/Plasticized Cassava Starch Blends - Henry C. Obasi; Isaac O. Igwe; Innocent C. Madufor (Advances in Materials Science and Engineering)
Polypropylene (PP)/plasticized cassava starch (PCS) blended with and without compatibilizer (polypropylene-graft-maleic anhydride (PP-g-MA)) via melt blending were prepared for soil burial which lasted for 90 days. Plasticized starch loadings of 0, 10, 20, 30, 40, and 50 wt.% were used, while pp-g-ma was used at 10 wt.% based on starch weight. The PP/PCS and PP/PCS/PP-G-MA blends were evaluated for their tensile properties. It was observed that the tensile strength, elongation at break, and young’s modulus decreased with increases in soil burial time as well as starch content for PP/PCS blends. Similar treads for the tensile properties were observed for PP/PCS/PP-g-MA, but with higher properties as compared to uncompatibilized blends. However, the tensile properties for both PP/PCS and PP/PCS/PP-g-Ma decrease with increases in starch loading and also as the burial period progressed.